(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In this article, views on books and reading in the 21st century technological age, innovations, bibliography and the goals and tasks set for the field, achievements achieved on the basis of new technologies, and plans for modern bibliography will be discussed. Social networks and their positive and negative effects on reading are discussed. Conclusions are given on how important the textbooks, training manuals and fiction literature created for members of society with limited opportunities are for today’s readers.